Contemporary transformations of intimacy in the perspective of Michel Foucault’s history of sexuality - Musiał, Maciej (Hybris, 2014)
This article discusses relations between Foucault’s history of sexuality and the contemporary transformations of eroticism diagnosed by Wojciech Klimczyk. The Klimczyk’s studies are interpreted in the perspective of theoretical tools provided by Foucault and seem to lead to an interesting conclusions. Peculiarity of those conclusions is especially connected with the fact that they are opposite to the diagnosis provided by Brian McNair and Anthony Giddens. Simply speaking, Giddens and McNair claim that contemporary intimacy is emancipated from most of regulations and contains a high amount of freedom, while Klimczyk (with theoretical support of Foucault) argues that nowadays sexuality is strongly regulated by the outside conditions, especially by the market.